Social and occupational security and labour market flexibility in Sweden: the case of unemployment compensation - Gabriella Sjögren Lindquist; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2007)
The Swedish labour market and social policy is aimed at facilitating flexibility in the labour market. The active labour market policy and the design of the social security pension system are two frequently mentioned examples of that policy. This does not necessarily mean that all policy programs are in accordance with the goal of enhancing flexibility. In this paper we analyze one part of the social and occupational (collectively bargained) security system - the compensation at unemployment with special emphasis on the schemes complementing compensation from the unemployment insurance scheme. We focus on the effects of those systems on labour market flexibility. Some parts of these complementing systems support mobility and return to work after layoffs, other parts of the systems may lead to that workers avoid job mobility and to prolonged periods of unemployment. Of special interest is that those complementing systems differ between different sectors of the labour market and that many, especially young people, are not covered.
Keywords: 330; Arbeitslosenversicherung; Arbeitslosigkeit; Arbeitsmobilität; Abfindung; Arbeitsmarktflexibilisierung; Schweden